LATIHAN LANGKAH PERSEGI DALAM PROGRAM MASYARAKAT BERBASIS POSYANDU UNTUK MENINGKATKAN KESEIMBANGAN PADA POPULASI LANSIA - Wijianto Wijianto; Hafidh Erli Nurdin Pratama; Hana Nuha Kurnia (ABISATYA : Journal of Community Engagement, 2025)
The elderly is the final phase in the human life cycle which is characterized by a decrease in body functions, such as weakness and balance disorders, which can increase the risk of falling and decrease independence. Therefore, promotive and preventive efforts through physical exercise are needed to maintain fitness and reduce the risk of falling. One of the exercises that has proven effective is the Square Stepping Exercise (SSE), which is a step pattern exercise from simple too complex to training postural and cognitive balance for the elderly. This community service program was carried out at the Ngudi Waras Elderly Posyandu, Senden, Tohudan, Colomadu, involving 30 elderly people aged 60-75 years. The activities carried out included counseling, demonstrations, SSE practices, and evaluation using dynamic balance test before and after interventions. The instruments used were in the form of participant characteristics forms and balance time test. Data analysis was carried out in a descriptive manner based on the BMI category due to the limited number of samples and activity design. Most participants were in the BMI category of overweight (13 people), followed by normal (11 people) and Underweight (6 People). The average time of the dynamic balance test showed improvement in all BMI categories after the implementation of SSE. These result show that SSE can improve the dynamic balance of the elderly without being affected by nutritional status. SSE is effective as a simple exercise that can be applied as a self-directed program at home to improve balance and contribute to the prevention of fall risk in the elderly.